Carbon nanotube covalent bonding mediates extraordinary electron and phonon transports in soft epoxy matrix interface materials. (February 2020) - Lee, Sanghoon; Suh, Daewoo; Kim, Wonjoon; Xu, Chenchen; Kim, Taehun; Song, Changsik; Yoo, Chijong; Kim, Youngsung; Kim, Joongnyon; Baik, Seunghyun
Abstract: Soft thermal interface materials (TIMs) are essential components for the thermal management of electrical and mechanical devices. However, the low thermal conductivity ( κ ) still limits efficient heat dissipation. Here we achieve a record high κ (101.7 W m −1 K −1 ) among soft isotropic TIMs, mediated by the covalent bonding between hydroxyl groups of multiwalled carbon nanotubes (MWNTs) and ester groups of soft epoxy (SE) matrix. It is important to maintain a high relative humidity (60%) during synthesis since the binding reaction is initiated by capturing a proton from environmental moisture. The covalent bonding uniformly distributes MWNTs (0.5 vol%) which construct percolation networks with additional Ag flake fillers (33.5 vol%). The solid electron and phonon contact at the interface is achieved by the coalescence between Ag flakes and Ag nanoparticles pre-functionalized on MWNTs (nAgMWNTs). This dramatically increases electron (11.9 nm) and phonon (105.7 nm) mean free paths and κ . The dispersion of nAgMWNTs is poor without the hydroxyl-ester binding, and the identical filler combination provides very low κ (9.7 and 0.9 W m −1 K −1 ) in polyurethane and silicone rubber matrices. The κ in SE matrix is 11, 300% greater than that in silicone rubber matrix. The soft isotropic nAgMWNT‒Ag flake‒SE TIM shows excellent heat dissipation performance of a cellular phone application processor. Graphical abstract: Image 1